Microsurgical services at the Department of Orthopaedic - Mohd Kasim, Kamil; Khalid, Kamarul Ariffin; Nazri, Mohd Yusof; Mohammad Amin, Mohammad Azril (2007)
Microsurgery is an area of specialization needed in the field of reconstruction. lt enables complex procedures like replantation, revascularization, free flaps and vascularised bone grafts to be done. The microsurgical services in our department started after the arrival of the microsurgical microscope in 2003. With the availability of such a service, we are able to independently deal with most of the complex and complicated injuries of the limbs with neurovascular involvement. This case series is our early experiences in handling such cases which require microsurgical expertise. To date, this centre has managed amputated, partially amputated limbs and vascular injuries with a reasonable success rate.